2003
DOI: 10.1080/09638231000118276
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal contact and the stigma of mental illness: A review of the literature

Abstract: Title: Interpersonal contact and the stigma of mental illness: A review of the literature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
360
2
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(396 citation statements)
references
References 42 publications
18
360
2
8
Order By: Relevance
“…The positive impact of training for mental health professionals has been previously described in literature (Couture & Penn, 2003;Nordt et al, 2006). However, there is also evidence that at least some aspects of mental health professionals' attitudes are more negative than those of the general public, e.g.…”
Section: Discussionmentioning
confidence: 93%
“…The positive impact of training for mental health professionals has been previously described in literature (Couture & Penn, 2003;Nordt et al, 2006). However, there is also evidence that at least some aspects of mental health professionals' attitudes are more negative than those of the general public, e.g.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have found that people with greater familiarity with mental disorders have lessstigmatizing attitudes. 27,28 In a previous study, mental health professionals had more positive attitudes towards medical students with mental disorders than health professionals not specialized in mental health. 26 Paradoxically, in our study, students with personal or family experience of a mental disorder and those who had visited a mental health institution were more likely to agree or strongly agree that mental disorders were grounds for dismissal from pharmacy school.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to these stigmatized groups greatly reduces the negative interactions from in-group members (Corrigan, Morris, Michaels, Rafacz, & Rusch, 2012;Couture & Penn, 2003). Trust can be established and stigma between in-groups and out-groups eliminated when contact is increased or someone with a mental illness becomes part of an in-group (Bornstein, 1989;Harmon-Jones & Allen, 2001;Lee, 2001;Zajonc, 1968;Bizub & Davidson, 2011).…”
Section: Stigma Erroneous Beliefs and Social Distancingmentioning
confidence: 99%